2009
DOI: 10.1152/japplphysiol.91058.2008
|View full text |Cite
|
Sign up to set email alerts
|

Short oxygen prebreathe periods reduce or prevent severe decompression sickness in a 70-kg swine saturation model

Abstract: Mahon RT, Dainer HM, Gibellato MG, Soutiere SE. Short oxygen prebreathe periods reduce or prevent severe decompression sickness in a 70-kg swine saturation model. J Appl Physiol 106: 1459-1463, 2009. First published January 29, 2009 doi:10.1152/japplphysiol.91058.2008 survivors are expected to achieve saturation with inert gas. However, rescue procedures may not accommodate staged decompression, raising the potential for severe decompression sickness (DCS). Alternatives to standard recompression therapy are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…On the day of the hyperbaric exposure (1 day after recovery from surgery), the subjects were placed into individual custom-designed Plexiglas boxes (26 ϫ 54 ϫ 38 in.) inside a steel-hulled, 450-ft. 3 hyperbaric chamber as reported elsewhere (21). Each box allowed for an adjustable atmosphere environment in which the subjects could breathe without requiring restraints.…”
Section: Experiments Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…On the day of the hyperbaric exposure (1 day after recovery from surgery), the subjects were placed into individual custom-designed Plexiglas boxes (26 ϫ 54 ϫ 38 in.) inside a steel-hulled, 450-ft. 3 hyperbaric chamber as reported elsewhere (21). Each box allowed for an adjustable atmosphere environment in which the subjects could breathe without requiring restraints.…”
Section: Experiments Protocolmentioning
confidence: 99%
“…Hyperbaric exposure. For the nine swine in which we induced DCS, the chamber was pressurized with air to 184 kPa (60fsw) at a rate of 92 kPa/min (30 fsw/min) and remained at depth for 15 h. It is our experience from our previous studies, following saturation diving at 184 kPa, 80% of animals experienced symptoms of DCS (21). For the remaining six control swine, the chamber was pressurized with air to 15 kPa (5 fsw) and remained at depth for 15 h. The control depth of 15 kPa was chosen to recreate all experimental conditions yet pose an extremely low risk of DCS.…”
Section: Experiments Protocolmentioning
confidence: 99%
“…We have previously demonstrated that " dropout decompression " (direct ascent to the surface from 22-h saturation at 18 msw) in a 15-swine cohort (mean weight 69.5 kg) resulted in 86.6% Type I cutis, 40% cardiopulmonary DCS, and 73.3% neurologic DCS ( 11 ). The anticipated occurrence of DCS in a dropout from 40 msw was anticipated to equal or exceed these rates.…”
Section: Resultsmentioning
confidence: 97%
“…On the day of the hyperbaric exposure, the subjects were placed into individual custom-designed Plexiglas ™ boxes (26 x 54 x 38 ) inside a steel-hulled hyperbaric chamber reported elsewhere ( 11 ). Each box allowed for a hyperbaric oxygen environment in which the subjects could breathe without requiring restraints.…”
Section: Pre-dive Preparationmentioning
confidence: 99%
See 1 more Smart Citation